Toxicopaphological Effects of Intravenous Injection of Layer Double Hydroxide (LDH) Nanoparticles in Male Rats - Samia Kh. Mahmood (Journal of Global Pharma Technology, 2020)
The rapid growth of using nanoparticles in different field of science, lead to the urgent necessity to study the toxicpathology of this submicron particle. Layer Double Hydroxide NPs have qualified features such as bio-compatibility, ion exchange and pH effect which make LDH NPs potential candidate for various biological applications such as drug delivery. Hence, in this study Mg-Al LDH NPs have been prepared by co precipitation method and injected intravenously. Twenty rats were divided into two groups as follows: Group I: Rats served as control and injected 1ml of distilled water intravenously for one month. Group II: Rats served as experimental and received by I/V injected in the tail vein 1ml of 0.00276 of Mg-Al LDH NPs g/ml. daily for one month. The sizes of LDH NPs have been measured by SEM which resulted size ranging between 50- 80nm in diameter. The liver, kidney, heart, lung, spleen and testes were examined histologically. The toxicopathological results were very severe in kidneys, lung, spleen and heart, while being moderate in liver and testes. In general, all organs showed necrotic changes with inflammatory cell infiltration, congestion and thrombosis in blood vessels.Keywords: LDH, Toxicopathological study, Nanoparticles, Rat.